Mitigation of Dietary Microplastic Accumulation and Oxidative Stress Response in Rainbow Trout (Oncorhynchus mykiss) Fry Through Dietary Supplementation of a Natural Microencapsulated Antioxidant - İdris Şener; Matteo Zarantoniello; Nico Cattaneo; Federico Conti; Luca Succi; Giulia Chemello; Elena Antonia Belfiore; Ike Olivotto (Animals)
Microplastic (MP) contamination in aquafeed poses a significant risk to fish health and safety. This study evaluated the effectiveness of a microencapsulated natural antioxidant, astaxanthin (AX), in mitigating the adverse effects of dietary MPs in rainbow trout fry. The microcapsules were composed of an organic wall matrix designed to preserve AX while limiting MP absorption in the intestine. During a 60-day feeding trial, fish were fed diets containing amino formaldehyde polymer fluorescent MP microbeads (1–5 µm; 50 mg/kg), either alone or in combination with microencapsulated AX. MP localization in tissues was assessed via confocal microscopy, and quantification was performed following chemical tissue digestion. Fish welfare was evaluated using histological and molecular analyses. No significant effects on growth or gut morphology were observed across experimental groups. However, MPs were mainly translocated to the liver, where they induced oxidative stress, as evidenced by the upregulation of sod1, sod2, and cat gene expression. The inclusion of microencapsulated AX significantly mitigated the oxidative stress response, and the microcapsules facilitated MP coagulation in the gut, reducing intestinal absorption. These findings highlight the potential of microencapsulated antioxidants to counteract MP-induced oxidative stress and reduce MP bioavailability in aquaculture species, contributing to improved fish welfare and product quality.